Manajemen POAC pada Masa Pandemi Covid-19 (Studi Kasus BDR di SMP Negeri 2 Praya Barat Daya) - Khairul Akbar; Hamdi Hamdi; Lalu Kamarudin; Fahruddin Fahruddin (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2021)
This study aimed to describe the implementation of learning from home (LFH) during the Covid-19 pandemic seen from the POAC (Planning, Organizing, Actuating, Controlling) management theory. The research used a qualitative approach with a case study method. The research was conducted at SMP Negeri 2 Praya Barat Daya, Central Lombok Regency, NTB. The research subjects involved the principal of the school, while the informants were teachers and students who were selected using purposive sampling technique. Data were collected through interviews and documentation. Data analysis used the Miles and Huberman model. The results showed that the principal implemented management functions in accordance with the POAC theory in the implementation of LFH, namely: 1) planning, which was identifying data of students having gadgets followed by designing online and offline LFH preparations; 2) organizing, which was dividing students into two study groups, namely the online group and the offline group; 3) actuating, which was introducing facilities and infrastructure used in online and offline learning, followed by its implementation of LFH; and 4) controlling, which was implementing the evaluation of the LFH program at the school level carried out at the end of the 2019/2020 school year.